Aplikasi Pemantau Perangkat Jaringan Berbasis Web Menggunakan Protokol SNMP dan Notifikasi SMS - Shofa Taftazanie; Agung Budi Prasetijo; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2017)
Device monitoring tool on a computer network is required by the administrator to perform management of the device. This research produces web applications using PHP that is capable of monitoring and collecting device information on the network. This app uses SNMP and Syslog protocols to perform monitoring on the device. Device information will be collected on the monitor server and displayed in web-based applications. This app using crontab to be able to monitor every minute. This application can also send a warning message in the form of SMS and email to the administrator when an error occurs on the device so that handling is expected to be faster done. This web application can make it easier for administrators to monitor devices anywhere.